Learning Strategies in Islamic Religious Education to Build Students' Spiritual Awareness and Islamic Ethics - Indriani, Dede; Chandra, Emelia; Jannah, Syakinatul; Gusmaneli, Gusmaneli (EDUCTUM: Journal Research, 2024)
Learning strategies in Islamic religious education have an important role in building students' spiritual awareness and Islamic ethics. In this context, a holistic approach that integrates cognitive, affective and psychomotor aspects is crucial, especially in today's digital era. Experiential learning, such as group worship activities, group discussions on moral values, and the use of technology and digital media to present material in an interesting and relevant manner, can help increase understanding of the internalization of Islamic teachings. In addition, the role of teachers as role models and facilitators who are able to create a conducive and inspiring learning environment greatly determines success. Thus, the application of effective learning strategies in Islamic religious education is expected to be able to form students who not only understand religious teachings theoretically, but also practice them in everyday life, so as to form individuals with high spiritual awareness and strong Islamic ethics.